PENGARUH LEADERSHIP STYLE TERHADAP INTELLECTUAL CAPITAL DALAM MENINGKATKAN FINANCIAL PERFORMANCE PADA HOTEL BINTANG TIGA, EMPAT DAN LIMA PADA SEKTOR PARIWISATA JAWA TIMUR - Monica Koharitanu; Sarce Elsye Hatane (Business Accounting Review, 2016)
This study aimed to examine the direct and significant influence of leadership style to intellectual capital, intellectual capital to financial performance, and leadership style to financial performance in the three, four and five-star Hospitality Sector in East Java. This study used quantitative approach and the data were obtained through the distribution of questionnaire to three-star hotel until five-star hotel in East Java. The data that were obtained, then processed by using PLS software. The result of this study showed that there was a positive and significant relationship of leadership style to intellectual capital, intellectual capital to financial performance, leadership style to financial performance in hospitality sector in East Java. Intellectual capital could become as intervening variable to leadership style and financial performance because of the direct relationship between leadership style and financial performance gave smaller influence than through intellectual capital.